2017
DOI: 10.3390/molecules22091441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rhamnetin as an Inhibitor of the Pharmacological Effect of Secretory Phospholipase A2

Abstract: Rhamnetin (Rhm), 3-O-methylquercetin (3MQ), and Rhamnazin (Rhz) are methylated derivatives of quercetin commonly found in fruits and vegetables that possess antioxidant and anti-inflammatory properties. Phospholipase A2 (PLA2) displays several important roles during acute inflammation; therefore, this study aimed at investigating new compounds able to inhibit this enzyme, besides evaluating creatine kinase (CK) levels and citotoxicity. Methylated quercetins were compared with quercetin (Q) and were incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
1
24
0
8
Order By: Relevance
“…Rhamnetin ( 6 ) is a methylated derivative of quercetin. The presence of 3OH on the C-ring of rhamnetin may contribute to both its anti-inflammatory and enzymatic inhibition of secretory phospholipase A2 (sPLA2), and the methylation of ring A may provide the increase in cell viability and a low creatine kinase (CK) level induced by sPLA2 [ 51 ]. These results showed that compound ( 6 ) could be a candidate as a natural compound for the development of new anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Rhamnetin ( 6 ) is a methylated derivative of quercetin. The presence of 3OH on the C-ring of rhamnetin may contribute to both its anti-inflammatory and enzymatic inhibition of secretory phospholipase A2 (sPLA2), and the methylation of ring A may provide the increase in cell viability and a low creatine kinase (CK) level induced by sPLA2 [ 51 ]. These results showed that compound ( 6 ) could be a candidate as a natural compound for the development of new anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the flavone family, but not the chalcones, have been reported to be positive modulators of mitochondrial biogenesis and function, although the mechanism of action remains unknown (21). Both classes of molecules can inhibit phospholipase A2 (PLA2) enzymes (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…From a molecular point of view, clove buds contain flavonoids like β-caryophyllene, kaempferol, and rhamnetin, which contribute to clove anti-inflammatory properties [ 85 , 86 , 87 , 88 , 89 ]. In experimental animal models, eugenol (at 200 and 400 mg/kg doses) was shown to reduce the volume of pleural exudates without changing the total count of blood leukocytes, which indicates the anti-inflammatory activity of this molecule [ 90 ].…”
Section: Clove ( Syzygium Aromaticum L) In Hermentioning
confidence: 99%